Joint Beamforming Design and Power Control Game for a MIMO Radar System in the Presence of Multiple Jammers - Wu, Jiale; Shi, Chenguang; Zhang, Weiwei; Zhou, Jianjiang (IEEE transactions on aerospace and electronic systems, 2024)
In this article, the problem of joint beamforming and power allocation in a multiple-input multiple-output (MIMO) radar network is investigated in the presence of signal-dependent interference and multiple jammers. Specifically, the main objective of the radar system is to improve the performance in terms of total power consumption and beampattern peak sidelobe level (PSL) under the signal-to-interference-plus-noise ratio (SINR) constraints at the radars, whereas the jammers aim to maximize their side effects on the radars. The interactions between the radar system and the jammers are formulated as a noncooperative game. An efficient iterative algorithm is proposed to minimize the total weighted transmit power of the radar system based on the Nash equilibrium of the game. In addition, in order to suppress the sidelobe level of both the transmit and receive beampatterns for the radars, this article further studies the problem of minimizing the sidelobe level by introducing a pricing mechanism that takes into account the accumulated sidelobe level of the radar system. The sidelobe control problems are effectively solved using the Lagrange duality and the Lagrange multiplier method. Finally, simulation results are provided to confirm the convergence of the proposed algorithms and assess the performance in terms of total power consumption and PSL.